Soundproofing Performance Evaluation of Panels Made of Fibers of Acrylonitrile Butadiene Styrene Copolymer (ABS). (2015) - Stanciu, Mariana Domnica; Curtu, Ioan; Cosereanu, Camelia; Lica, Dumitru
Abstract: Industrial development and intensive mechanization of all production processes, multiplication and diversification of transport, development of traffic flows in urban and extra-urban areas, all lead to the increased noise in terms of intensity, frequency, duration of exposure to noise. In these circumstances, a global interest goes to the monitoring and analysis of the road traffic noise maps and to the noise and vibration sources. Thus, several European and national directives on the road traffic noise and beyond have been introduced, including guides and noise assessment methods. The paper aims to present the acoustic behavior of composite panels made from chips resulted in the milling process of acrylonitrile butadiene styrene (ABS), in terms of sound proofing performance in connection with the factors which affect the sound insulation of noise level. The panels with the sizes of 300x300x15 up to 20 mm were produced by hot pressing the ABS chips, at a temperature of 100 - 110 °C for 10 minutes. The link between chips was achieved by melting point of acrylonitrile. The experimental tests investigated: the influence of the distance between source and the noise barrier formed by the composite material made from ABS; the influence of the noise level emitted by the source; the influence of the distance between the sound barrier and the receptors placed collinear with the source; the influence of the position of receptors against the lateral ends of the barrier; the influence of the barrier angle relative to vertical plane of symmetry. The research highlighted the acoustic performance of composites made from ABS waste, innovative products, which can be considered an ecological, technological and economic solution in obtaining the core of acoustic barrier structures. Increased thickness of ABS fiberboard or combined with other absorbent material can lead to the increase of sound absorption coefficient and to obtain superior acoustic performances.